2012
DOI: 10.4021/jmc390w
|View full text |Cite
|
Sign up to set email alerts
|

Kernohan-Woltman Notch Phenomenon Related to Chronic Subdural Hematoma: A Case Report

Abstract: Kernohan-Woltman notch phenomenon defines the neurological picture caused by a compressive injury of the cerebral peduncles at the tentorial edge due to the contralateral supratentorial lesion and leads to ipsilateral hemiparesis or hemiplegia and mydriasis. We have represented this case of Kernohan-Woltman notch phenomenon that developed secondary to chronic subdural hematoma in a 88-year-old patient as a very rarely reported case. We conclude that advanced brain atrophy contributes to the formation of Kernoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…4,7 Several study by Kernohan and Woltman in 1929 described that any supratentorial mass may produce a significant compression to the contralateral cerebral peduncles where anatomically is adjacent to the tentorial edge. 1 It has also been reported that the compression that caused injury of corticospinal tracts in the contralateral cerebral peduncles may cause the ipsilateral weakness, in the course of Kernohan's notch syndrome. 2 However, there is no comprehensive clinical trial which elaborate the incidence of Kernohan's notch syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…4,7 Several study by Kernohan and Woltman in 1929 described that any supratentorial mass may produce a significant compression to the contralateral cerebral peduncles where anatomically is adjacent to the tentorial edge. 1 It has also been reported that the compression that caused injury of corticospinal tracts in the contralateral cerebral peduncles may cause the ipsilateral weakness, in the course of Kernohan's notch syndrome. 2 However, there is no comprehensive clinical trial which elaborate the incidence of Kernohan's notch syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…It was in 1929, Kernohan and Woltman first demonstrated compression of the cerebral peduncle against the free edge of the tentorium. [1][2][3] They studied the gross and microscopic appearance of 276 brains with tumor and showed 34 (12%) with various "degrees of notching" of the cerebral peduncle. 3 Also, they reported a case of patient with left supratentorial brain tumor with left hemiparesis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations